2021
DOI: 10.1098/rsob.210142
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of stalked and acorn barnacle adhesive proteomes

Abstract: Barnacles interest the scientific community for multiple reasons: their unique evolutionary trajectory, vast diversity and economic impact—as a harvested food source and also as one of the most prolific macroscopic hard biofouling organisms. A common, yet novel, trait among barnacles is adhesion, which has enabled a sessile adult existence and global colonization of the oceans. Barnacle adhesive is primarily composed of proteins, but knowledge of how the adhesive proteome varies across the tree of life is unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 93 publications
(209 reference statements)
0
23
0
Order By: Relevance
“…In this view, the cp68k identified by Kamino (2006) may be a cp43k-like protein for their similar amino acid compositions. Several latest omics investigations further confirmed that these different types of BCPs are widespread in different barnacle species ( Domínguez-Pérez et al, 2021 ; Lin et al, 2021 ; Schultzhaus et al, 2021 ). Notably, apart from these major BCPs, there remains a trace amount of other components such as enzymes and small molecules in barnacle cement, which have not been fully characterized yet.…”
Section: Adhesion Principles Of Barnacle Cementmentioning
confidence: 85%
“…In this view, the cp68k identified by Kamino (2006) may be a cp43k-like protein for their similar amino acid compositions. Several latest omics investigations further confirmed that these different types of BCPs are widespread in different barnacle species ( Domínguez-Pérez et al, 2021 ; Lin et al, 2021 ; Schultzhaus et al, 2021 ). Notably, apart from these major BCPs, there remains a trace amount of other components such as enzymes and small molecules in barnacle cement, which have not been fully characterized yet.…”
Section: Adhesion Principles Of Barnacle Cementmentioning
confidence: 85%
“…For proteolytic digestion with trypsin, 60 cycles of PCT were conducted at 45°C, 45 kpsi for 50 seconds, with 10-second pauses between cycles. Liquid chromatography, tandem mass spectrometry (LC-MS/MS) was performed on a Orbitrap Fusion Lumos Tribrid mass spectrometer coupled to an Ultimate 3000 nanoRSLC system (Thermo Scientific, Waltham, MA, USA), as previously described 54-55 . Mass spectrometry data were transformed and raw data extracted into peak lists via in-house scripting 56 .…”
Section: Methodsmentioning
confidence: 99%
“…Although it remains to be confirmed that WSP exists in seawater, these findings suggest that WSP is released into the environment. WSP was also detected from a stalked barnacle, Pollicipes pollicipes (Schultzhaus et al, 2021), suggesting that a phylogenetically wide variety of barnacles use WSP to attract conspecific cyprids. Recent studies indicate that there are several homologs of WSP (So et al, 2017;Abramova et al, 2019;Schultzhaus et al, 2019;Schultzhaus et al, 2020;Schultzhaus et al, 2021).…”
Section: Introductionmentioning
confidence: 98%
“…Another pheromone, WSP, purified from adults of A. amphitrite diffuses into seawater when embedded in an agarose gel, suggesting that it attracts cyprids on a relatively larger spatial scale (Endo et al, 2009;Clare, 2010). In addition, WSP was identified from cement of adult A. amphitrite (So et al, 2017;Schultzhaus et al, 2019;Schultzhaus et al, 2020;Schultzhaus et al, 2021), which indicates that WSP exists in the adhesive layer of adult barnacles. Although it remains to be confirmed that WSP exists in seawater, these findings suggest that WSP is released into the environment.…”
Section: Introductionmentioning
confidence: 99%